2015
DOI: 10.1097/ico.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

Potential New Modes of Treatment of Neurotrophic Keratopathy

Abstract: The cornea focuses external light onto the retina, a function for which it must be transparent and possess a smooth surface. Homeostasis of the corneal epithelium is regulated by various humoral factors present in the tear fluid and by neural factors derived from the trigeminal nerve. Neurotrophic keratopathy (NK) is characterized by corneal epithelial disorders that result from impairment of trigeminal nerve function and a consequent deficiency of neural factors. The ideal mode of treatment for this condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 46 publications
1
18
0
2
Order By: Relevance
“…The experimental evidence that SP is able to promote corneal healing has prompted some small open‐label clinical studies in patients with NK, which demonstrated an efficacy of topical SP associated with IGF‐1 treatment in in promoting corneal wound healing. Subsequently, topical SP and IGF‐1 treatment were evaluated in a larger, open‐label study in 25 patients with NK, achieving a complete corneal healing in 73% of patients after 4 weeks of treatment (Brown et al, ; Chikama et al, ; Nishida et al, ; Yamada et al, ; Yanai et al, ).…”
Section: Role Of Corneal Innervation In the Maintenance Of A Healthymentioning
confidence: 99%
“…The experimental evidence that SP is able to promote corneal healing has prompted some small open‐label clinical studies in patients with NK, which demonstrated an efficacy of topical SP associated with IGF‐1 treatment in in promoting corneal wound healing. Subsequently, topical SP and IGF‐1 treatment were evaluated in a larger, open‐label study in 25 patients with NK, achieving a complete corneal healing in 73% of patients after 4 weeks of treatment (Brown et al, ; Chikama et al, ; Nishida et al, ; Yamada et al, ; Yanai et al, ).…”
Section: Role Of Corneal Innervation In the Maintenance Of A Healthymentioning
confidence: 99%
“…Antibiotic drops are needed to prevent bacterial infections in addition to ocular surface lubrication. Options include corneal and scleral contact lenses,29 a lateral tarsorrhaphy, botulinum A toxin into the levator muscle or amniotic membrane transplantation to cover the non-healing epithelial defect 30. Treatment of stage 3 disease is directed at stopping the stromal melting to prevent perforation 31.…”
Section: Introductionmentioning
confidence: 99%
“…As such, current therapy is directed toward alleviating symptoms as they appear. Some commonly used treatments include artificial tears, bandage contact lenses, punctual occlusion, autologous serum tears, tarsorrhaphy, and amniotic membrane grafting (Nishida and Yanai, 2009; Yanai et al, 2015). Local administration of neural factors such as substance-P (SP), particularly in combination with insulin-derived growth factor-1 (IGF-1), has been shown to promote epithelial cell migration and closure of persistent epithelial defects in the setting of NK (Yanai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some commonly used treatments include artificial tears, bandage contact lenses, punctual occlusion, autologous serum tears, tarsorrhaphy, and amniotic membrane grafting (Nishida and Yanai, 2009; Yanai et al, 2015). Local administration of neural factors such as substance-P (SP), particularly in combination with insulin-derived growth factor-1 (IGF-1), has been shown to promote epithelial cell migration and closure of persistent epithelial defects in the setting of NK (Yanai et al, 2015). Nerve growth factor (NGF) has also been shown to promote wound healing and induce nerve regeneration in neurotrophic corneas but local adverse effects have limited its use (Nishida and Yanai, 2009).…”
Section: Introductionmentioning
confidence: 99%